Key Determinants of US policy towards Kashmir under President George W. Bush: - Ashraf Maqbool, Shahzada (IJRDO - Journal of Social Science and Humanities Research, 2016)
One of the cardinal factors that distanced India from the United States during the cold war period, was the latter’s policy towards Kashmir. Since foreign or third party intervention in the Kashmir issue has always been unacceptable to India, the frequent US attempts to intervene and seek a resolution of the issue naturally generated resentment in India. After the cold war ended with the disintegration of Soviet Union in 1990-91, the US lost its interest in South Asia and consequently, appeasing Pakistan-its cold war ally, no longer remained its overarching concern. And, though the concern for prevention of proliferation of nuclear weapons prevented the US from totally abandoning South Asia, the post-cold war world order, nevertheless, offered new opportunities to both the US and India to revisit their estranged relationship. The paper attempts to show how the US change in its Kashmir policy served as a catalyst in finally bringing a rapprochement in Indo-US relations. It argues that the US, especially under George Bush deliberately avoided to seek solution of the Kashmir issue, apart from attempting to facilitate negotiations between India and Pakistan. The policy of de-hyphenation that the Bush administration sought to pursue in relation to India and Pakistan, in effect put Kashmir out of the bounds for the US.